Pengembangan Sistem Informasi Manajemen Homestay berbasis Web Studi Kasus Omah Kweni Homestay - Dwiky Rifandianto; Djoko Pramono; Bondan Sapta Prakoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Omah Kweni Homestay is a homestay accommodation located in the Bantul area of Yogyakarta city, which is a tourist city and can be a business opportunity in the hospitality industry. The homestay faces operational problems that are still conventionally managed, such as using a notebook that results in unreliable data storage, and the creation of reservation and warehouse reports takes a long time. To address these problems, a proposed solution is to develop a management information system that can assist in homestay management. The system development targets receptionists, roomboys, marketers, and managers. The Waterfall development method is used in this study because it is suitable for the homestay's parallel business processes where homestay requirements do not change. The use of the Waterfall development method is carried out in 4 stages. The needs analysis phase produces 6 business process models, 11 system features, 36 functional requirements and 1 non-functional system requirements, and 9 use cases and use case scenarios. The system design stage produces 9 Sequence Diagrams, 8 Class Diagrams consisting of class controllers and class models, 1 Physical Data Model, and 7 Wireframes. The system implementation stage results in the implementation of the design in the previous stage. The system testing phase using the black-box testing method produced 15 test cases and compatibility testing using the SortSite 6 Trial application with the results of 8 minor issues, User Acceptance Testing produced a percentage index of 90% for receptionists, 91.42% for marketing, 92.5% for Roomboy, and 97.14% for manager. The results of the user acceptance test show that all users agree with the development of the information system being developed.